Pengembangan Media Pembelajaran Uno Physics Card Menggunakan Model Pembelajaran Team Games Tournament Materi Gaya dan Hukum Newton - Eka Rosita Sari; Fatkhur Rohman; Effendi Effendi (Pendidikan Fisika Universitas Nurul Huda, 2022)
This study is a research and development research and development (R&D) which aims to determine the development of learning media for uno physics card using the team games tournament learning model for Newton's law and style material, knowing the level of validity of the Uno Physics Card learning media using the Team Games Tournament learning model on style material. and Newton's laws, and knowing the level of practicality of the media This development research adopted the 4-D model, which only focuses on the define, design and develop stages and Location used in this study, namely at MTs Al-Hikmah Purwodadi with a sample of 20 students from class VIII. The results of this study indicate that the validity value obtained by the Uno Physics Card media and its supporters has an average validation index of high validity classification. The practicality test of the UNO Physics Card media by students is 83%